High‐sensitivity C‐reactive Protein is a Predictive Factor of Adiposity in Children: Results of the Identification and prevention of Dietary‐ and lifestyle‐induced health Effects in Children and InfantS (IDEFICS) Study - Nappo, Annunziata (Blackwell Publishing Ltd, 2013)
BACKGROUND: Whereas cross‐sectional studies have shown that obesity is associated with increased C‐reactive protein (CRP) levels in children, little is known about the impact of low‐grade inflammation on body mass changes during growth. METHODS AND RESULTS: We assessed cross‐sectionally and longitudinally the association of high‐sensitivity (hs)‐CRP levels with overweight/obesity and related cardiometabolic risk factors in the Identification and prevention of Dietary‐ and lifestyle‐induced health Effects in Children and InfantS (IDEFICS) cohort. 16 224 children from 8 European countries (2 to 9 years) were recruited during the baseline survey (T0). After the exclusion of 7187 children because of missing hs‐CRP measurements and 2421 because of drug use during the previous week, the analysis was performed on 6616 children (Boys=3347; Girls=3269; age=6.3±1.7 years). Of them, 4110 were reexamined 2 years later (T1). Anthropometric variables, blood pressure, hs‐CRP, blood lipids, glucose and insulin were measured. The population at T0 was divided into 3 categories, according to the baseline hs‐CRP levels. Higher hs‐CRP levels were associated with significantly higher prevalence of overweight/obesity, body mass index (BMI) z‐score and central adiposity indices (P values all <0.0001), and with higher blood pressure and lower HDL‐cholesterol levels. Over the 2‐year follow‐up, higher baseline hs‐CRP levels were associated with a significant increase in BMI z‐score (P<0.001) and significantly higher risk of incident overweight/obesity. CONCLUSIONS: Higher hs‐CRP levels are associated to higher body mass and overweight/obesity risk in a large population of European children. Children with higher baseline levels of hs‐CRP had a greater increase in BMI z‐score and central adiposity over time and were at higher risk of developing overweight/obesity during growth.